Some Problems of Business Ethics: Islamic Point of View (Philosophy and Progress, 2019)
Business ethics is one of the important branches of applied ethics. Many thinkers including ethicists, economists, academicians and philosophers have tried to explore necessary principles, standards, rules and regulations for business-related issues. Islam, a major religion of the world, has prescribed, from its very inception, necessary rules and principles for every aspect of life including business and commerce-related dealings. This paper explores Islamic concepts of business, its principles, rules and regulations. From the Islamic point of view, this paper shows that business is not merely a job of profit-making, but also an ibadah (worship). Moreover, it claims that Islamic business ethics is not only concerned with moral soundness of business persons, but also closely connected with the salvation of man.Philosophy and Progress, Vol#61-62; No#1-2; Jan-Dec 2017 P 67-92